A Critical Mapping of Community Engaged Learning In Canadian Public Universities - Smeltzer, Sandra; Poli, Amala; Pieber, Darryl; Rockandel, Hailey; Ferrucci, Giada; Spraggon, Mackenna (Canadian Journal of Higher Education / Revue canadienne d'enseignement supérieur)

(untitled) (Canadian Society for the Study of Higher Education, 2026)
Community engaged learning (CEL) is an increasingly important collaborative form of experiential learning (EL) within Canadian higher education. This article critically examines the landscape of CEL within publicly funded universities across Canada. As EL gains traction across the country, CEL emerges as a unique response to varied social exigencies amidst the corporatization of academia. Ethically coordinated CEL can address societal challenges and nurture conscientious citizens, but navigating the complexities of CEL programming demands substantial resources and a commitment to reflective practices. Through a comprehensive scan of university websites and strategic plans, our research reveals myriad approaches to CEL terminology, institutional commitments, and community engagement. The study identifies key pathways for future research and calls for the establishment of a national network to facilitate collaboration and advance the collective understanding and impact of CEL in Canada.